IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN UNTUK PENILAIAN KINERJA KARYAWAN MENGGUNAKAN METODE HYBRID SAW DAN AHP BERBASIS WEB - Rizky, Ahmad; Ariadi, Fadly (JUPIK : Jurnal Penelitian Ilmu komputer, 2025)
In the era of globalization and increasingly tight business competition, objective and measurable employee performance assessments are an important need for companies, including Toko Ady Alam Accessories, which is engaged in the retail accessories sector. Manual performance assessments cause various obstacles such as subjectivity, lack of transparency, and the absence of clear criteria. This study aims to design and implement a web-based Decision Support System (DSS) using the Hybrid AHP (Analytical Hierarchy Process) and SAW (Simple Additive Weighting) methods. The development method used is Waterfall, with data collection techniques through observation, interviews, and literature studies. The results of this study The implementation of a web-based system for assessing employee performance using the Hybrid SAW and AHP methods is able to accelerate the employee evaluation process objectively and systematically. The designed computerized system has succeeded in increasing the efficiency of employee data management at Toko Ady Alam Accessories by providing automation features that facilitate input, updating, and monitoring data in real-time, thus reducing dependence on manual processes.